Role of hydrologic information in stochastic dynamic programming: a case study of the Kemano hydropower system in British Columbia - Desreumaux, Quentin; Côté, Pascal; Leconte, Robert (Canadian journal of civil engineering, 2014)
This paper presents a study describing the effect of various hydrological variables in stochastic dynamic programming (SDP) for solving the optimization problem of managing a hydropower system. We will show how choosing the best hydrological variables can strongly affect management policies. This is especially true for the system studied here, namely the Kemano hydroelectric system located in British Columbia, Canada, which is subject to large streamflow volumes due to significant snow cover during winter. Real-time snow water equivalent (SWE) data can be used directly as a variable in SDP management policies. Results indicate that for the system in this study, the maximum SWE (i.e., highest level of SWE observed from the start of winter to the current decision period) is the best among the methods investigated for effective, safe management, compared with Markov or order p autoregressive models when forecasts are not available.